Spectroscopic properties (FT-IR, NMR and UV) and DFT studies of amodiaquine - Pélagie Manwal A Mekoung; Alhadji Malloum; Munusamy Govindarajan; Rose Ngono Mballa; Issofa Patouossa; Auguste Abouem A Zintchem; Charles P.N. Nanseu; Ibrahim N. Mbouombouo (Heliyon, 2023)
Amodiaquine (AQ) was synthesized by a condensation reaction and characterized by experimental FT-IR, 1H and 13C nuclear magnetic resonance (NMR) and UV spectroscopies. In the present work, Density Functional Theory (DFT) calculations.The structural and spectroscopic (FT-IR, 1H and 13C NMR and UV) data of amodiaquine molecule in ground state have been investigated by using Density Functional Theory (DFT). The calculations have been performed at the using B3LYP method with 6–311++G(d,p) and 6–311++G(2d, p) basis sets theory level were performed, first, to confirm its structure, then to explain its reactive nature through its molecular properties such as natural charges, local and global reactivity descriptors or natural bond orbital (NBO). Afterwards, the calculated properties were compared with experimental results. The 1H and 13C NMR chemical shifts were calculated by using the gauge-independent atomic orbital (GIAO) method, while the electronic UV–Vis spectrum is predicted using the time-dependent density functional theory (TD-DFT). Globally, the computerized results showed good agreement close similarity with the experimental values. The molecular properties such as natural charges, local and global reactivity descriptors, molecular electrostatic potential (MEP), natural bond orbital (NBO) of title molecule were calculated insights into the stability, reactivity and reactive sites on the molecule.The calculated energy band gap (ELUMO-EHOMO) value of AQ was found to be 4.09 eV suggesting that it could be considered as a hard molecule with high stability, supported by global reactivity descriptors. Molecular electrostatic potential (MEP) analysis revealed heteroatoms (oxygen and nitrogen) as the most putative nucleophilic sites when hydrogen atoms to which they are linked appear as electrophilic sites. The potential use of amodiaquine as non-linear optical (NLO) material and its thermodynamic indicators have also been assessed.